Do the multiplication, then take the square root. After the multiplication, you get 28x4y2. The square root of 28 is 2 times the root of 7, the square root of x4 is x2, and the root of y2 is y. So, the final result is 2 Times Square root of 7, times x2y.
âˆš18xy = âˆš(9*2xy) = âˆš9*âˆš2xy = 3*âˆš(2xy)
(x + 4y)(x - 6y)
(x-y)2 is a square so (x-y)2 >= 0 expanding, x2 - 2xy + y2 >= 0 so x2 + y2 >= 2xy or 2xy <= x2 + y2
4xy - 2xy
yes * * * * * No, it isn't. 2xy = 2 times x times y. Depending on which you mean: 2x2y = 2 times x times 2 times y = 4xy; OR 2x2y = 2 times x times x times y.
(x - y)2 >= 0 since the left hand side is a square. ie x2 - 2xy + y2 >= 0 so x2 + y2 >= 2xy
Can't be solved without knowing what x and y are. You can factor out 6y though. The expression then becomes: 6y * squareroot(2xy)
(x + y)2 = x2 + 2xy + y2
Since 2xy is a factor of 2x2y, it is automatically the GCF.
2xy + 6xy = 8xy
x2 + y2 = x2 - 2xy + y2 + 2xy = (x - y)2 + 2xy = 72 + 2*8 = 49 + 16 = 65 You could, instead, solve the two equations for x and y and substitute, but the above method is simpler.
it would equal 2xy
(x + y + z)2 = x2 + y2 + z2 + 2xy + 2yz + 2zx
the difference between 2x2 +4xy-3 and x2-2xy-4 is?
8x2= 16 16-2xy=14xy 14xy-3y(2)= 11x 11xX2= 22x Answer - 22x............... Happy Birthday ! (;
3xy and 2xy. You can see that 3xy and 2xy have something in common with each other. They both have xy and the end of them. Hope this helped.
What is : 5xy- x2t + 2xy + 3x2t
The three terms are: -3xy2, 2xy and -4y3
Neither of those expressions is a binomial. [ 2y + 2xy ] is a binomial.